2016
DOI: 10.1111/jar.12293
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Health and Well‐Being of Adults With Conditions of a Genetic Origin: Views from Professionals, Syndrome Support Groups and Parents

Abstract: BackgroundAdvances in medical genetics herald the possibility that health and social care services could be more responsive to the needs arising from a person's genotype. This development may be particularly important for those men and women whose learning disability (known internationally as intellectual disability) is linked to a neurodevelopmental condition of genetic origin.MethodThis possibility is tested through interviews with samples of (i) professional ‘opinion former’ with nationally recognised clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For example, the prevalence of AS (1:10,000-40,000) [ 30 ] is considerably lower than that for FXS (1:5,000) [ 31 ]. The current article does not allow for a description of the genetic cause or phenotype of each individual syndrome but excellent descriptions are available in Table 1 of [ 32 ] and within the wider literature.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the prevalence of AS (1:10,000-40,000) [ 30 ] is considerably lower than that for FXS (1:5,000) [ 31 ]. The current article does not allow for a description of the genetic cause or phenotype of each individual syndrome but excellent descriptions are available in Table 1 of [ 32 ] and within the wider literature.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the National Institute for Health and Care Excellence guidelines have increasingly emphasized the importance for a person‐centred approach in clinical practice for individuals with intellectual disabilities. However, research has also highlighted the usefulness of recognizing an individual's diagnosis when providing personalized health and social care . For example, several studies have identified the differing profiles of communication between genetic syndromes, which suggests that the genetic basis plays a role in the nature of impairments .…”
Section: Discussionmentioning
confidence: 99%
“…However, research has also highlighted the usefulness of recognizing an individual's diagnosis when providing personalized health and social care. 48 For example, several studies have identified the differing profiles of communication between genetic syndromes, which suggests that the genetic basis plays a role in the nature of impairments. 5,6,49 Martin et al 6 showed differing profiles across a number of language domains for individuals with fragile X and Down syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they apparently turned to caregivers to facilitate communication and manage behaviours likely to upset hospital routines. Moreover, there is a danger that, by focusing on "reasonable adjustments" to minimize, the impact of reported challenges might eclipse no less significant biomedical complexities such as: comorbid health conditions (Cooper et al, 2015), polypharmacy (Haider, Ansari, Vaughan, Matters, & Emerson, 2014), and rare neuro developmental conditions (Redley, Pannebakker, & Holland, 2018). However, while likely to satisfy family members' desire for involvement, there could also be some unintended adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, their constant presence may contribute to the evidence that, contrary to the Mental Capacity Act, medical practitioners (and other clinicians) believe that family members can make decisions on behalf of any adult identified as a person with an intellectual disability. Moreover, there is a danger that, by focusing on "reasonable adjustments" to minimize, the impact of reported challenges might eclipse no less significant biomedical complexities such as: comorbid health conditions (Cooper et al, 2015), polypharmacy (Haider, Ansari, Vaughan, Matters, & Emerson, 2014), and rare neuro developmental conditions (Redley, Pannebakker, & Holland, 2018). That the clinical needs of patients with intellectual disabilities are at risk of being overlooked should be of serious concern because they appear to be associated with sub-optimal care and treatment.…”
Section: Discussionmentioning
confidence: 99%